Infernape uncovers cell type–specific and spatially resolved alternative polyadenylation in the brain - Kang, Bowei; Yang, Yalan; Hu, Kaining; Ruan, Xiangbin; Liu, Yi-Lin; Lee, Pinky; Lee, Jasper; Wang, Jingshu; Zhang, Xiaochang (Genome Research, 2023)
Differential polyadenylation sites (PAs) critically regulate gene expression, but their cell type–specific usage and spatial distribution in the brain have not been systematically characterized. Here, we present Infernape, which infers and quantifies PA usage from single-cell and spatial transcriptomic data and show its application in the mouse brain. Infernape uncovers alternative intronic PAs and 3′-UTR lengthening during cortical neurogenesis. Progenitor–neuron comparisons in the excitatory and inhibitory neuron lineages show overlapping PA changes in embryonic brains, suggesting that the neural proliferation–differentiation axis plays a prominent role. In the adult mouse brain, we uncover cell type–specific PAs and visualize such events using spatial transcriptomic data. Over two dozen neurodevelopmental disorder–associated genes such as Csnk2a1 and Mecp2 show differential PAs during brain development. This study presents Infernape to identify PAs from scRNA-seq and spatial data, and highlights the role of alternative PAs in neuronal gene regulation.